Acute Exacerbation Impairs Right Ventricular Function in COPD Patients - (:unkn) unknown (My University, 2015)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) may impair right ventricular (RV) function. Tissue Doppler imaging (TDI) is helpful in the noninvasive evaluation of RV longitudinal function. The aim of this study was to assess the impact of acute COPD exacerbation on RV function assessed by TDI. METHODS: The study included 30 COPD patients who had acute exacerbation and 30 controls. RV function was assessed echocardiographically during acute exacerbation and after recovery. In addition to conventional echocardiographic parameters, tricuspid annular plane systolic excursion, tricuspid annulus peak systolic velocity (Sa), and TDI-derived isovolumic myocardial acceleration (IVA) were determined. RESULTS: During exacerbation, COPD patients had a significantly larger RV and higher pulmonary artery systolic pressure, with significantly lower IVA, Sa and tricuspid annular plane systolic excursion compared to controls. After recovery, IVA and Sa significantly increased, while RV diameter and pulmonary artery systolic pressure significantly decreased to levels similar to controls. There were statistically significant, but modest correlations between IVA and Sa (r=0.441, p=0.003), tricuspid annular plane systolic excursion (r=0.628, p<0.001), pulmonary artery systolic pressure (r=-0.391, p=0.002) and RV diameter (r=-0.309, p=0.018). Sa correlated with pulmonary artery systolic pressure (r=-0.350, p=0.007) and RV diameter (r=-0.344, p=0.008). CONCLUSIONS: COPD exacerbations have a negative impact on RV function. TDI-derived IVA and Sa may be used in the assessment of subclinical RV dysfunction in COPD patients with exacerbation.
Keywords: Female; Humans; Middle Aged; Aged; Male; Ventricular Dysfunction, Right; Risk Factors; Echocardiography, Doppler; Tricuspid Valve; Pulmonary Disease, Chronic Obstructive